2003
DOI: 10.1111/1467-9280.01453
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Number Sense

Abstract: Four experiments investigated infants' sensitivity to large, approximate numerosities in auditory sequences. Prior studies provided evidence that 6-month-old infants discriminate large numerosities that differ by a ratio of 2.0, but not 1.5, when presented with arrays of visual forms in which many continuous variables are controlled. The present studies used a head-turn preference procedure to test for infants' numerosity discrimination with auditory sequences designed to control for element duration, sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
145
1
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 605 publications
(158 citation statements)
references
References 27 publications
2
145
1
10
Order By: Relevance
“…The former, approximate and nonverbal capacity is shared across many species (for reviews, see Nieder & Dehaene, 2009;Agrillo & Beran, 2013;Pahl et al, 2013) and, at least in basic form, is thought to be present from birth in humans (e.g., Xu & Spelke, 2000;Lipton & Spelke, 2003).…”
Section: Evolutionary and Cultural Factors In Numerical Cognitionmentioning
confidence: 99%
“…The former, approximate and nonverbal capacity is shared across many species (for reviews, see Nieder & Dehaene, 2009;Agrillo & Beran, 2013;Pahl et al, 2013) and, at least in basic form, is thought to be present from birth in humans (e.g., Xu & Spelke, 2000;Lipton & Spelke, 2003).…”
Section: Evolutionary and Cultural Factors In Numerical Cognitionmentioning
confidence: 99%
“…If the magnitude of the ratio is small, for example, 15 dots versus 16 dots (15:16 ratio), responses tend to be slower than in the easy ratio condition, and the accuracy is typically lower (Barth, et al., 2003; Cordes, Gelman, Gallistel, & Whalen, 2001; Pica, Lemer, Izard, & Dehaene, 2004), indicating harder comparison. Converging evidence from developmental and comparative studies as well as studies with people whose languages do not have number words shows ratio‐dependent performance on nonsymbolic number comparison tasks suggesting a key feature of the ANS: independence from language (Cantlon, Brannon, Carter, & Pelphrey, 2006; Izard, Sann, Spelke, & Streri, 2009; Libertus and Brannon, 2009; Lipton & Spelke, 2003; Nieder, 2009; Pica et al., 2004; Xu & Spelke, 2000). …”
Section: Introductionmentioning
confidence: 99%
“…Researchers in these fields have found that the ability to discriminate between different numbers of objects appears to be a foundational cognitive ability and have documented this ability in numerous species across the Animal Kingdom. For example, quantity discrimination has been demonstrated experimentally in several species of fish [5,11,[19][20][21], amphibians [8,22,23], birds [18,[24][25][26][27][28][29][30][31][32][33][34][35], mammals [9,[36][37][38][39][40][41], primates [42][43][44][45], human infants [46][47][48][49] and even some invertebrates [50][51][52]. The only study testing quantity discrimination in a reptile found that although ruin lizards (Podarcis sicula) do spontaneously select the larger quantity of food, they do not spontaneously select the option with a higher number of food items [53].…”
Section: Introductionmentioning
confidence: 99%